Amendment 14 civil rights of citizens. - Cambridge Educational (Firm) (Monmouth Junction, N.J. : Cambridge Educational, 2003)
This program explores the fourteenth amendment: its orgins, real-world applications, history of interpretation in the nation's courts, and implications for the future. Combining computer graphics, original live-action video, historical artwork, and archival footage with narration and interviews, this program illustrates the importance of the amendments in the history of the United States.
Title from container.
Keywords: United States; Constitutional amendments -- United States; Civil rights -- United States